Measurement of Hospital Performance in the Border Region of Timor Leste through Customer Satisfaction Aspects - Redjo, Paulina Rosna Dewi; Kase, Marce Sherly (Jurnal Samudra Ekonomi dan Bisnis, 2023)
Kefamenanu Regional General Hospital is the only government hospital in North Central Timor Regency (TTU) as a provider of health services in Kefamenanu City which is a border area. The current presence of the Leona Private Hospital in the district directly forces the Kefamenanu Hospital to improve services so as not to lose credibility in the community. Kefamenanu General Hospital must strive to provide quality health services for the community by formulating a vision, mission, goals, objectives and indicators of success as outlined in a strategic plan. In this article the discussion focuses on aspects of customer satisfaction. The results of the study show that from the perspective of customer satisfaction, it is in the "Satisfied" interval so that the performance of Kefamenanu Hospital can be said to be "Good".